ANALISIS KETELADANAN GURU UNTUK MENINGKATKAN PEMAHAMAN NILAI MORAL DAN KESETARAAN GENDER PADA SISWA MADRASAH - Irayanti, Irma; Sulkipani, Sulkipani; Sapriya, Sapriya (Center of Gender Studies and Child of State Islamic Institute of Metro, 2023)
This research aims to analyze the role of teacher exemplarity in enhancing the understanding of moral values and gender equality among high-level Madrasah Ibtidaiyah students. The research method employed was qualitative research with a case study approach. Data were collected through in-depth interviews with Madrasah teachers in high-level classes and participatory observations of teacher-student interactions in the classroom. The research findings indicate that teacher exemplarity significantly influences students' understanding of moral values and gender equality. Teachers who serve as examples through ethical behavior and respect for gender equality inspire students to internalize these values in their daily lives. Moreover, teacher exemplarity facilitates open dialogues on moral and gender equality issues in the classroom, aiding students in gaining a deeper understanding of these concepts. This research provides essential insights into how the teacher exemplarity approach can be used as an effective strategy to enhance students' understanding of moral values and gender equality in Madrasah education. The practical implications of this study underscore the importance of teachers as positive role models in shaping students' characters and promoting gender equality in the context of Madrasah Ibtidaiyah education at the higher level. Keywords: Gender Equality, Teacher Exemplarity, Moral Values, Madrasah Students Abstrak Penelitian ini bertujuan untuk menganalisis peran keteladanan guru dalam meningkatkan pemahaman nilai moral dan kesetaraan gender pada siswa Madrasah Ibtidaiyah kelas tinggi. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam dengan guru Madrasah di kelas tinggi dan observasi partisipatif terhadap interaksi guru-siswa di kelas. Hasil penelitian menunjukkan bahwa keteladanan guru memiliki pengaruh yang signifikan dalam membentuk pemahaman siswa tentang nilai moral dan kesetaraan gender. Guru yang menjadi teladan dalam perilaku etis dan penghormatan terhadap kesetaraan gender dapat menginspirasi siswa untuk menginternalisasi nilai-nilai tersebut dalam kehidupan sehari-hari mereka. Selain itu, keteladanan guru juga memfasilitasi dialog terbuka tentang isu-isu moral dan kesetaraan gender di kelas, membantu siswa dalam memahami konsep-konsep ini secara lebih mendalam. Penelitian ini memberikan wawasan yang penting tentang bagaimana pendekatan keteladanan guru dapat digunakan sebagai strategi efektif dalam meningkatkan pemahaman nilai moral dan kesetaraan gender pada siswa Madrasah. Implikasi praktis dari penelitian ini adalah pentingnya peran guru sebagai model yang baik dalam membentuk karakter siswa dan mempromosikan kesetaraan gender dalam konteks pendidikan Madrasah Ibtidaiyah di kelas tinggi. Kata Kunci: Kesetaraan Gender, Keteladanan Guru, Nilai Moral, Siswa Madrasah